RANCANG BANGUN SISTEM APLIKASI RESERVASI HOTEL BERBASIS WEB PADA HOTEL KAPITO RAJA - Ruseno, Ndaru; Irfansyah, Dicki; Nursiaga, Rahmat; Santoso, Imam (Journal of Mathematics and Technology (MATECH), 2024)
As a form of computer use and systems, the system has become the most important task in order to improve company performance. So every system process that runs well can be replaced with a better system, because it provides more conceptual and sophisticated information and can support the decision making process. With the provisions of the information system at the company, it can prevent data loss and facilitate employees in carrying out the company's business processes. Currently KAPITO HOTEL does not have an information system that can support business needs. Through relevant methods and information, the results of this study are the need for hotel reservation applications that can support the needs and employees. Web-based applications are expected to improve performance at the Kapito Hotel.